COST OPTIMIZATION IN AGRIBUSINESS BASED ON LIFE CYCLE COSTING - Savić, Bojan; Milojević, Ivan; Petrovic, Vesna (Economics of Agriculture, 2019)
In efforts to achieve and sustain competitiveness and contribute to the goal of sustainable development of society, entity management requires information that will enable the adoption of adequate decisions. The changed business environment and the growing importance of the issues that emerge from the domain of traditional business, both spatial and temporal, have necessitated the monitoring of costs not only during the production phase, but throughout the entire grain cycle of the product. Since conventional cost accounting systems do not have the capacity to generate the above information, in theory and practice, a life cycle costing system (LCC) has been developed. The aim of the paper is to point out the specificity and importance of perceiving and capturing the impacts and consequential costs that arise during the life cycle of the product, with particular reference to agribusiness, precisely because of the complexity of optimizing costs in that sector.